Aspectos teóricos da violência estrutural urbana - Santos Junior, Eduardo Honório dos (2014)
The urban study is related to the notion of continuity of the different threatening conditions to physical, biological and socio wellness of the built space. The occupational dimension was observed with advanced techniques in Geographic Information System (GIS) and evaluated from the degree of accessibility and mobility directly guided by the patterns and processes of constructed space in which mobile and immobile elements are ordered. Both the environment people live in a state of continuous and profound environmental changes and the dynamic urban conditions. The urban space continues with a negative balance in the set of network that has been modernized in the current metropolitan system, the dynamics of urban structure is compromised by mobility circularity and municipal boundaries that the road network and its vectored patterns are actively oriented to the ecological conditions of the current state of the critical socio-organization. The city of Aracaju and its metropolitan area are the main determinants as complementary arrangements of roads and require a reorganization to improve their access and mobility implying its broadest extension. A solution to the urbanized space can be suggested starting from necessary and urgent reform of the metropolitan road network aiming fluidity and distribution of space and movement.